2011
DOI: 10.3109/02770903.2011.626482
|View full text |Cite
|
Sign up to set email alerts
|

Child and Caregiver Involvement and Shared Decision-Making during Asthma Pediatric Visits

Abstract: Objective The purpose of this study was to examine: (a) the extent to which caregivers and children asked asthma management questions during pediatric asthma visits, (b) the extent to which providers engaged in shared decision-making with these caregivers and children, and (c) the factors associated with question-asking and shared decision-making. Methods Children ages 8 through 16 with mild, moderate, or severe persistent asthma and their caregivers were recruited at five pediatric practices in non-urban ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 28 publications
3
66
2
1
Order By: Relevance
“…Similar to the findings from studies about other populations, [263][264][265][266][267] the clinicians in this study reported that communication about ADRs was generally important in clinical practice. However, in specific cases they described filtering the information that they discussed with families.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to the findings from studies about other populations, [263][264][265][266][267] the clinicians in this study reported that communication about ADRs was generally important in clinical practice. However, in specific cases they described filtering the information that they discussed with families.…”
Section: Discussionsupporting
confidence: 80%
“…The research assistant explained the study, obtained caregiver consent and child assent, and administered the eligibility screener. 9 Providers and families were told that the study was examining communication during pediatric visits. All of the medical visits were audio-tape recorded.…”
Section: Participantsmentioning
confidence: 99%
“…Using data from the study' s eligibility screening instrument, asthma severity was classified as mild versus moderate/severe by a research assistant based on the caregiver' s report of the child' s recent symptoms and medication use. [7][8][9] Our eligibility screening instrument used the primary asthma severity classification system that was in use when the study was designed and conducted. [7][8][9] More detail about the asthma severity classification system is provided by Sleath et al 9 A variety of demographic and sociocultural factors were examined as potential confounders.…”
Section: Demographic and Sociodemographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations